The Correlation between the Character and Self-Efficacy of Pre-service Biology Teachers - Astuti Muh. Amin; Ilham Majid; Noor Hujjatusnaini; Romi Adiansyah (Postgraduate, University of Mataram, 2023)
Self-efficacy has a positive influence on students’ character values. The current study explored the correlation between the character and self-efficacy of pre-service biology teachers. This study used a correlation research method and involved all biology education students from Ternate, North Maluku, Indonesia. The research sample comprised 120 biology education students from IAIN Ternate and STIKIP Kie Raha, Ternate, North Maluku. The research instruments were divided into types: (1) a questionnaire and observation sheets to evaluate student character and (2) a questionnaire and observation sheets to measure student self-efficacy. All instruments had undergone expert and empirical validation processes and reliability tests. The study results revealead a significant correlation between students’ self-efficacy and character with rcalculated of 0.917 and a significance value of 0.000 < 0.05. This finding suggests that increased self-efficacy may lead to an increase in student character. The results of this study can contribute to efforts to strengthen students’ character and self-efficacy through applying a learning model.